1993
DOI: 10.1038/361453a0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-plasminogen activator is induced as an immediate–early gene during seizure, kindling and long-term potentiation

Abstract: The requirement of protein and messenger RNA synthesis for long-term memory suggests that neural activity induced by learning initiates a cascade of gene expression. Here we use differential screening to identify five immediate-early genes induced by neuronal activity. One of these is tissue-plasminogen activator (tPA), an extracellular serine protease, which is induced with different spatial patterns in the brain by three activity-dependent events: (1) convulsive seizure increases expression of tPA in the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
536
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(563 citation statements)
references
References 25 publications
16
536
1
2
Order By: Relevance
“…10 It has been suggested that these neurotoxic effects of tPA are independent of its desirable thrombolytic action. 10 These findings, although in contradiction with previously suggested physiological roles of tPA in brain development, 12 learning, memory, 13 and long-term potentiation, 14,15 have challenged the concept of tPA lytic therapy for stroke. Whether tPA treatment for ischemic stroke may be neurotoxic has become a controversial issue in the treatment of stroke patients.…”
contrasting
confidence: 51%
“…10 It has been suggested that these neurotoxic effects of tPA are independent of its desirable thrombolytic action. 10 These findings, although in contradiction with previously suggested physiological roles of tPA in brain development, 12 learning, memory, 13 and long-term potentiation, 14,15 have challenged the concept of tPA lytic therapy for stroke. Whether tPA treatment for ischemic stroke may be neurotoxic has become a controversial issue in the treatment of stroke patients.…”
contrasting
confidence: 51%
“…Smad3/4 has a prominent role in regulating the expression of proteins involved in neuronal survival/death, differentiation, and plasticity (reviewed in Sanyal et al, 2004;Gomes et al, 2005). One of the Smad3/4-regulated protein targets is plasminogen activator inhibitor type-1 (PAI-1, also referred to as Serp1), which binds and inactivates tissue-type plasminogen activator (tPA), a multifaceted protein implicated in neurite outgrowth (Krystosek and Seeds, 1981), neuronal migration (Moonen et al, 1982;Seeds et al, 1999), learning (Qian et al, 1993;Seeds et al, 1995), excitotoxicity (Tsirka et al, 1995), synaptic plasticity (Baranes et al, 1998;Fiumelli et al, 1999;Neuhoff et al, 1999), stress response , and pathogenesis of mood disorders (Eskandari et al, 2005;Tsai, 2006). Using small interfering RNA (siRNA) and dominant negative mutants specific to GSK-3α and GSK-3β, we recently reported that GSK-3α inhibition causes an upregulation of Smad3/4-dependent transactivation and PAI-1 protein levels, while inhibition of GSK-3β induces a downregulation of Smad3/4 transactivation and PAI-1 expression (Liang and Chuang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, plasminogen activators have been shown to be produced and secreted by neurons and glia and to participate in remodeling events that occur during cell migration (Moonen et al, 1982), neurite outgrowth (Monard, 1988;Pittman and Williams, 1989;Sumi et al, 1992;Sappino et al, 1993), and synaptic plasticity (Monard, 1988;Qian et al, 1993;Sappino et al, 1993). MSP Table 1.…”
Section: Region and Cell-specific Expression Of Msp In The Cnsmentioning
confidence: 99%
“…The localized release of plasminogen activators by neuronal growth cones has suggested that their expression and subsequent degradation of extracellular matrix components is required for neurite outgrowth (Krystosek and Seeds, 1981). Tissue plasminogen activator (tPA) mRNA expression in hippocampal neurons is increased with afferent stimulation (Qian et al, 1993;C arroll et al, 1994), and, in the mouse mutant weaver, cerebellar neurons can be rescued from death in vitro by the serine protease inhibitor aprotinin (Murtomaki et al, 1995). Transgenic mice deficient in tPA exhibit an altered form of long-term potentiation (Frey et al, 1996) and are resistant to excitotoxic-mediated neuronal degeneration (Tsirka et al, 1995(Tsirka et al, , 1997.…”
mentioning
confidence: 99%
See 1 more Smart Citation